Pemanfaatan Tepung daun Indigofera (Indigofera zollingeriana Miq) sebagai pakan untuk meningkatkan produksi dan kualitas internal telur Ayam KUB - Usman Usman; Suharno Suharno; L. I. Zebua; P. Sujarta (Universitas Bengkulu, 2023)
One of the variants of native chicken that is quite potential to be developed in Indonesia is the KUB chicken. The quality and production of free-range chicken eggs can be increased by providing quality feed. One alternative source of quality feed is the use of Indigofera zollingeriana leaves. This study aims to determine the increase in egg production and internal quality by adding Indigofera zollingeriana Leaf Flour (ILF) in KUB chicken rations. This study used a completely randomized design (CRD) consisting of 5 treatments, namely R0 (control), R1 (7.5% ILF), R2 (15.0% ILF), R3 (22.25% ILF), and R4 (30.0% ILF) and 6 replicates. Observation parameters include Feed Conversion Ratio (FCR), egg production, egg weight, Hen Day Production (HDP), and internal egg quality. The results showed that adding ILF significantly increased production, internal egg quality, and ration conversion but had no significant effect on ration consumption. The highest increase in egg production was obtained by treatment with 15% and 22.5% ILF, with HDP 53.87%. The increase in egg weight quality, egg yolk index, white egg index, and egg yolk color were highest in the treatment with 30% ILF compared to the control. Giving ILF 22.5% gave the lowest FCR value compared to other treatments. It was concluded that providing ILF in the ration significantly increased egg production and internal quality in KUB chickens.